Protection Against Trademark Holders In The Case of Jolibi Trademark PT Tatalogam Lestari - Kus Prih Bandono; Markoni Markoni; Joko Widarto; Nardiman Nardiman (Sociological Jurisprudence Journal, 2024)
The development of a business in a country. Brands have an important role as a differentiator in the midst of goods and service activities in society. For business actors, a brand is an image and a good name for a company. The presence of Law Number 20 of 2016 concerning Marks and Geographical Indications aims to provide legal certainty for registered marks and have legal protection for registered marks, as well as to resolve disputes related to marks. One example in the research is the case study of decision number 39/Pdt.Sus-Merek/2023.PN.Niaga.Jkt.Pst between Jollibee Foods Corporation and PT Tatalogam Lestari. This research aims to examine issues related to the position and legal power of patented brand holders in Indonesia in accordance with the MIG Law and the form of legal protection for patented brand holders related to the lawsuit process in commercial courts. The research method used in this research is normative juridical research with a statutory and analytical approach that uses primary legal materials. The research results show that in the case of a brand dispute between Jollibee, owned by Jollibee Foods Corporation, and Jolibi, owned by PT Tatalogam Lestari, the brand registered first (first to file) has legal force because it is registered in the Intellectual Property Database of the Ministry of Law and Human Rights. Registered trademarks are entitled to protection for ten years and can be extended if the trademark in question is still used and circulating in Indonesia, as well as the form of legal protection for trademark holders in the study of decision number 39/Pdt.Sus-Merek/2023.PN.Niaga.Jkt.Pst. The panel of judges at the court of first instance decided that they rejected the plaintiff's claim in its entirety because the plaintiff could not prove the argument that it was a well-known mark, the form of legal protection for registered marks, namely, the protected mark of the party who registered the essentially the same or similar mark would definitely not be able to be registered, protection from applicants who have bad intentions, and protection by being able to file a lawsuit to cancel the deletion of a mark for a brand that has bad intentions.